DEVELOPMENT OF COMIC-BASED TEACHING MATERIALS TO IMPROVE THE MATHEMATICAL CRITICAL THINKING ABILITY OF FIFTH-GRADE ELEMENTARY SCHOOL STUDENTS - Latifah, Leti; Arifuddin, Ahmad; Andini, Wulan; Waliyadin, Waliyadin (PD PGMI se Indonesia, 2024)
This research changed students' low critical mathematical thinking abilities. To overcome this problem, researchers developed comic-based teaching materials to enhance college students' critical mathematical thinking skills. This study aims to supply comic-based coaching materials that are legitimate and practical. This research uses the R&D method with a 4D development model. This research design uses data collection techniques, validation sheets, and practicality questionnaire sheets. The subjects in this research were 20 students in class V. From the research results, it was found that the media expert's score was 96.66%, which was categorized as very appropriate. The linguist scored 88% in the very appropriate category, the material expert was 80% in the proper category, and the teacher practitioner was 92% in the very appropriate category. For the practicality of comic-based teaching materials, the teacher's practicality score was 96%, and the students' practicality score was 87.7%, categorized as very practical. Therefore, comic-based teaching materials can be used as a solution for educators to improve critical mathematical thinking.